1997
DOI: 10.1017/s0952523800011597
|View full text |Cite
|
Sign up to set email alerts
|

Single-neuron activity in the dorsomedial frontal cortex during smooth-pursuit eye movements to predictable target motion

Abstract: A region of dorsomedial frontal cortex (DMFC) has been implicated in planning and executing saccadic eye movements; hence it has been referred to as a supplementary eye field (SEF). Recently, activity related to executing smooth-pursuit eye movements has been recorded from the DMFC, and microstimulation here has been shown to evoke smooth eye movements. This report documents neuronal activity present in smooth-pursuit tasks where the predictability of target motion was manipulated. The activity of many neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 44 publications
(66 reference statements)
7
88
0
Order By: Relevance
“…We have found activation in this area previously for both types of eye movement when making predictive eye movements to a single target (Burke & Barnes, 2008). Other studies have found this area has been mainly associated with very short-term memory acquisition for single target locations (Heinen & Liu, 1997), and one previous study with prediction (Schmid et al, 2001). Our MVPA results demonstrate that this area is important in both saccades and pursuit during early motor learning for a series of movements.…”
Section: Multivariate Analysissupporting
confidence: 74%
“…We have found activation in this area previously for both types of eye movement when making predictive eye movements to a single target (Burke & Barnes, 2008). Other studies have found this area has been mainly associated with very short-term memory acquisition for single target locations (Heinen & Liu, 1997), and one previous study with prediction (Schmid et al, 2001). Our MVPA results demonstrate that this area is important in both saccades and pursuit during early motor learning for a series of movements.…”
Section: Multivariate Analysissupporting
confidence: 74%
“…Pursuit-related neurons are found in the cerebral cortex including the medial superior temporal visual area, frontal and supplementary eye fields, and ventral intra-parietal area (Sakata et al 1983;MacAvoy et al 1991;Colby et al 1993;Heinen and Liu 1997;Bremmer et al 2002;. Although upward and downward optic flows may be different in the natural environment, preferred directions for individual pursuit neurons in these cortical areas are distributed virtually evenly for all directions, making it difficult to explain the directional asymmetry observed in our study solely on the basis of cortical smooth-pursuit mechanisms .…”
Section: Possible Neural Correlates For the Directional Asymmetry In mentioning
confidence: 68%
“…Our laboratory has reported that chemical inactivation of the supplementary eye fields (SEF) in adult monkeys reproduced the directional asymmetry that had been compensated developmentally, suggesting that the SEF may be involved in the compensation . Although the exact neural mechanisms for the compensation and reappearance of the directional asymmetry induced by SEF inactivation are still unknown, preferred directions for individual SEF pursuit neurons are distributed virtually evenly for all directions (Heinen and Liu 1997;Fukushima et al 2004). Therefore, it is difficult to explain the reproduced directional asymmetry solely by loss of SEF output signals.…”
Section: For Dorsal Vermis Purkinje Cells) the Floccular Region Consmentioning
confidence: 99%
“…It acts as a timer, with activity that rises during the course of a trial. This process is based on activity recorded in SEF from preparatory or anticipation cells (Heinen and Liu, 1997). The fixation and anticipation components in the model interact in a mutually inhibitory manner.…”
Section: Discussionmentioning
confidence: 99%